SUSTAINABLE DEVELOPMENT: CHALLENGES FOR MALAYSIAN LOCAL GOVERNMENT - Sulzakimin Hj. Mohamed (Penerbit UTHM, 2016)
Local Governments today faced with a very demanding and dynamic situation in development agenda. They are now experiencing continuous challenges in term of implementing of sustainable development as in the environmental, economical and social aspect. Over the past decade, those aspects are discussed comprehensively and nowadays, as a result of this development, the interests in sustainable development are increasing. This book focuses on the issues of knowledge transfer practices towards sustainable development in Malaysia’s Local Governments. The book is published because the lack of books that revolve around issues of knowledge transfer practices towards sustainable development and Malaysian Local Governments. This book aims among students majoring in construction management in higher education in Malaysia. The word sustainable development and Malaysian Local Governments are chosen as the title of this book is to emphasize those issues and hopefully can increase awareness among Malaysian.